Evaluation of the antidiabetic property of aqueous leaves extract of Zanthoxylum armatum DC. using in vivo and in vitro approaches - Carey Vana Rynjah; Ningthoujam Neelima Devi; Nasheman Khongthaw; Donkupar Syiem; Suktilang Majaw (Journal of Traditional and Complementary Medicine, 2018)
The present study was designed to evaluate the antidiabetic potential of the aqueous leaves extract of Zanthoxylum armatum DC. leaves using in vivo and in vitro approaches. For in vivo studies, blood glucose level was monitored at different intervals after administration of varying doses of the extract for its hypoglycemic (100–6000 mg/kg b.w.) and antihyperglycemic (250 mg/kg b.w.) effect in normoglycemic and diabetic mice. In vitro enzymatic inhibition activity was tested against α-amylase, α- and β-glucosidase and lipase. Additionally hydroxyl radical, hydrogen peroxide scavenging assay and phytochemical screening were also performed. Element analysis of the plant was studied by Atomic Absorption Spectrometry (AAS) and Inductively Coupled Plasma Atomic Emission Spectrometer (ICP-AES). The plant extract showed significant hypoglycemic and antihyperglycemic effect in normoglycemic and diabetic mice. The IC50 values of extract for α-amylase, β-glucosidase, lipase, hydroxyl radical scavenging activity, hydrogen peroxide scavenging activity were 7.40 mg/ml, 0.30 mg/ml, 8.35 mg/ml, 3.25 mg/ml, 9.62 mg/ml respectively and the percentage of inhibition for α-glucosidase was 79.82% at 0.8 mg/ml. In vitro studies were compared with their respective standards. Elemental analysis revealed the presence of essential elements such as Mg, V, Fe, Cr, Zn, Cu, Mo, Mn, K, Ca, P and Sr which are all known to play a role in regulating blood glucose. The results demonstrate that Z. armatum aqueous leaves extract possess antidiabetic property in both in vivo and in vitro condition.